Population of white shrimp (Penaeus merguiensis) in a mangrove ecosystem, Belawan, North Sumatra, Indonesia - Indah Widiani; Ternala Alexander Barus; Hesti Wahyuningsih (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Widiani I, Barus TA, Wahyuningsih H. 2021. Population of white shrimp (Penaeus merguiensis) in a mangrove ecosystem, Belawan, North Sumatra, Indonesia. Biodiversitas 22: 5367-5374. White shrimp (Penaeus merguiensis De Man) is an essential fishery commodity with high economic and ecological value in the coastal area of North Sumatra. The main objective of this study was to determine the density of white shrimp in each harvesting area and to evaluate the current physicochemical factors in the Belawan mangrove ecosystem, North Sumatra, Indonesia. Four sampling sites were chosen as study areas. White shrimps were caught using ambai nets with a dimension of 4.5×4.5 m in width and 17 m in length placed from 4:00 - 7:00 PM. Measurement of physicochemical characteristics of sampling sites was conducted in situ and in the laboratory. Based on our study, the highest shrimp density was documented in the fishpond area (station 1) (89 ind/m2), while the lowest density was from the mangrove ecosystem area (station 2) (28 ind/m2). Based on the length class, the population of white shrimps was dominated by 16-18 mm shrimps. The gonad maturity level of the white shrimp population was classified into level 1 (The absence of thin-to-thick threads along the dorsal lining indicated the lowest gonad maturity level). White shrimps exhibited negative allometry in growth with a clumped pattern in population dispersion within the study area. The physicochemical parameters in four sampling sites, such as phosphorus content (P), and nitrate (NO3), exceeded the standard national quality set by the Ministry of Environment and Forestry.